2017
DOI: 10.1371/journal.pone.0177214
|View full text |Cite
|
Sign up to set email alerts
|

Novel avian paramyxovirus (APMV-15) isolated from a migratory bird in South America

Abstract: A novel avian paramyxovirus (APMV) isolated from a migratory bird cloacal swab obtained during active surveillance in April 2012 in the Lagoa do Peixe National Park, Rio Grande do Sul state, South of Brazil was biologically and genetically characterized. The nucleotide sequence of the full viral genome was completed using a next-generation sequencing approach. The genome was 14,952 nucleotides (nt) long, with six genes (3’-NP-P-M-F-HN-L-5’) encoding 7 different proteins, typical of APMV. The fusion (F) protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…Similar findings have been reported in previous studies where maximum nucleotide homology among these avulaviruses (1, 9, 12, 16, 17, previous studies also observed the existence of evolution in avulaviruses (Miller et al, 2009;Xiao et al, 2009;Bui et al, 2014). Susceptibility of diverse host species to all avulaviruses also supports transmission and evolution of avulaviruses (Dimitrov et al, 2016), reasoning the emergence of novel avulaviruses (14, 15, 17, 18, 19 and 20) from various wild/water-fowls in the recent years (Thampaisarn et al, 2017;Thomazelli et al, 2017;Lee et al, 2017;Neira et al, 2017;Karamendin et al, 2017). It is important to indicate that two avulaviruses (MF594548 and KY452442) are reported simultaneously from two different host species and geographical regions.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar findings have been reported in previous studies where maximum nucleotide homology among these avulaviruses (1, 9, 12, 16, 17, previous studies also observed the existence of evolution in avulaviruses (Miller et al, 2009;Xiao et al, 2009;Bui et al, 2014). Susceptibility of diverse host species to all avulaviruses also supports transmission and evolution of avulaviruses (Dimitrov et al, 2016), reasoning the emergence of novel avulaviruses (14, 15, 17, 18, 19 and 20) from various wild/water-fowls in the recent years (Thampaisarn et al, 2017;Thomazelli et al, 2017;Lee et al, 2017;Neira et al, 2017;Karamendin et al, 2017). It is important to indicate that two avulaviruses (MF594548 and KY452442) are reported simultaneously from two different host species and geographical regions.…”
Section: Discussionsupporting
confidence: 88%
“…Among them, the avulaviruses 1-9 were identified before the 80s; 10-13 were reported up to 2015, whereas 14, 15, 16, 17, 18, 19 and 20 are novel avulaviruses. These novel and emerging avulaviruses are reported recently from wild/water fowls (Thomazelli et al, 2017;Lee et al, 2017;Neira et al, 2017;Karamendin et al, 2017). Interestingly, these avulaviruses (10, 11, 12, 13, 14, 15, 16, 17, 18, 19 and 20 in particular) were isolated during avian influenza (AI) surveillance in wild birds (Miller et al, 2010;Briand et al, 2010;Terregino et al, 2013;Yamamoto et al, 2015;Thampaisan et al, 2017;Thomazelli et al, 2017;Lee et al, 2017;Neira et al, 2017;Karamendin et al, 2017).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Avian paramyxoviruses that have been isolated from birds; however, due to changes in taxonomy is now referred to as avian avulavirus (AAvV) (Amarasinghe et al., ). There are 13 described AAvV serotypes (AAvV‐1 to ‐13) based on neuraminidase inhibition tests and hemagglutination inhibition (HI), and eight another putative serotypes have been recently isolated (AAvV‐14 to ‐21) (Jeong et al., ; Lee et al., ; Neira et al., ; Thampaisarn et al., ; Thomazelli et al., ; Yamamoto, Ito, & Ito, ). While very limited information is known about the biological and molecular characteristics of AAvV‐2 to ‐21, extensive study has been mainly conducted on AAvV‐1 (Newcastle disease virus, NDV) (Cardenas‐Garcia et al., ; Umali, Ito, Katoh, & Ito, ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2015-2017 the reports were published about the discovery of seven novel serotypes of the APMV: from wild geese in Japan [5], Kazakhstan [6] and Ukraine [7], threefromducks in Japan [8], Korea [9] and from sandpiper in Brazil [10]; three more viruses were simultaneously isolated from antarctic penguins [11]. These data suggest that APMV are actively circulating in the wild avifauna and there is a high probability of the occurrence of other pathogenic variants.…”
mentioning
confidence: 99%